2020
DOI: 10.1111/1759-7714.13325
|View full text |Cite
|
Sign up to set email alerts
|

Unique metastasis‐associated lncRNA signature optimizes prediction of tumor relapse in lung adenocarcinoma

Abstract: Background Local relapses and metastases are primary causes of death in lung cancer patients. In the present study, we aimed to develop a prognostic signature based on metastasis‐associated lncRNAs in patients with lung adenocarcinoma (LUAD). Methods Firstly, the potential metastasis‐associated lncRNAs were identified by analyzing high‐throughput data from The Cancer Genome Atlas (TCGA), and based on which, an lncRNA signature was constructed for prediction of relapse in LUAD patients using Cox proportional ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…Hence, identifying effective lncRNAs to predict the prognosis of cancer patients has gradually attracted various levels of scientific research. Moreover, researchers have explored many lncRNA predictive models to determine the prognosis of tumor patients including liver cancer, pancreatic cancer, lung cancer, esophageal cancer, colorectal cancer, breast cancer, among others ( Gu et al, 2018 , 2019 ; Zhao et al, 2018 ; Liu et al, 2019 ; Ma and Deng, 2019 ; Zhou et al, 2019 ; Shen et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). A study by Ma found that four lncRNA signature can effectively distinguish high-risk and low-risk patients in liver cirrhosis and liver cancer patients thereby accurately predict the prognosis of liver cancer patients ( Ma and Deng, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, identifying effective lncRNAs to predict the prognosis of cancer patients has gradually attracted various levels of scientific research. Moreover, researchers have explored many lncRNA predictive models to determine the prognosis of tumor patients including liver cancer, pancreatic cancer, lung cancer, esophageal cancer, colorectal cancer, breast cancer, among others ( Gu et al, 2018 , 2019 ; Zhao et al, 2018 ; Liu et al, 2019 ; Ma and Deng, 2019 ; Zhou et al, 2019 ; Shen et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). A study by Ma found that four lncRNA signature can effectively distinguish high-risk and low-risk patients in liver cirrhosis and liver cancer patients thereby accurately predict the prognosis of liver cancer patients ( Ma and Deng, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the search for immune-related lncRNA in liver cancer may provide a new target for HCC treatment. Current researches have explored many lncRNA signatures associated with tumor prognosis ( Gu et al, 2018 ; Zhao et al, 2018 ; Zhou et al, 2019 ; Li et al, 2020 ; Shen et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). However, fewer lncRNA signatures have been identified in liver cancer since many studies focus on microRNAs and mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…OS and DFS of lncRNA LINC02323 high expressions were lower than those of lncRNA LINC02323 low expression, which is consistent with the LINC02323‐mediated metastasis of ovarian cancer. Zhang et al showed that LINC01819 signature had a regulatory role in the lung adenocarcinom cell mobility 16 …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Our previous study has shown that six lncRNAs, including LINC02323, are associated with metastasis and prognosis of LUAD. 19 Herein, we hypothesized that LINC02323-miRNA-target pathway might participate in the process of EMT and metastasis of LUAD. However, the exact mechanisms and pathways still remain unclear.…”
Section: Introductionmentioning
confidence: 99%